2019
DOI: 10.3389/fmars.2019.00025
|View full text |Cite
|
Sign up to set email alerts
|

Impact of “The Blob” and “El Niño” in the SW Baja California Peninsula: Plankton and Environmental Variability of Bahia Magdalena

Abstract: Warming Effects on a Mexican Coastal Lagoon diatoms. Algal blooms were composed by species adapted to high temperatures and nutrients depletion in 2015, while in 2016 and 2017 were composed by ruderalstrategist species and they were boosted by the nutrient pulses associated with the spring upwellings. The fall algal bloom, typical of subtropical coastal lagoons, was observed only in 2016 and it was confined to the interior of the lagoon where there are local inputs of nutrients. In 2015 and 2016 there was a su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
23
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(31 citation statements)
references
References 47 publications
4
23
0
4
Order By: Relevance
“…Our hydrographic analysis for nearshore waters in nBC clearly shows that, after removing the mean annual cycle, SST anomalies were approximately 2.0°C warmer under the 2014‐HW conditions, decreased through the 2015 upwelling season, and finally, reached values > 2.5°C when El Niño was already present in the coastal zone (Figures 5a and 5b; Table 1). These results are comparable to those previously reported for the southern section of the CCS (e.g., Durazo et al., 2017; Jiménez‐Quiroz et al., 2019; Kahru et al., 2018; Rudnick et al., 2017; Zaba & Rudnick, 2016). Zaba and Rudnick (2016) and Gentemann et al.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Our hydrographic analysis for nearshore waters in nBC clearly shows that, after removing the mean annual cycle, SST anomalies were approximately 2.0°C warmer under the 2014‐HW conditions, decreased through the 2015 upwelling season, and finally, reached values > 2.5°C when El Niño was already present in the coastal zone (Figures 5a and 5b; Table 1). These results are comparable to those previously reported for the southern section of the CCS (e.g., Durazo et al., 2017; Jiménez‐Quiroz et al., 2019; Kahru et al., 2018; Rudnick et al., 2017; Zaba & Rudnick, 2016). Zaba and Rudnick (2016) and Gentemann et al.…”
Section: Discussionsupporting
confidence: 92%
“…closely linked to the strong stratification promoted by the warm waters during the 2014-HW and El Niño (Figures 4c, 5g, and 5h;Gómez-Ocampo et al, 2017, 2018Gonzalez-Silvera et al, 2020), as well as reduced upwelling in spring-summer of 2015 ( Figure 4b; Jiménez-Quiroz et al, 2019;Robinson, 2016). Both conditions inhibited the regular upward flux of nutrients to the euphotic zone (Figures 4d, 5e, and 5f; Gonzalez- Silvera et al, 2020;Jacox & Edwards, 2011;Jacox et al, , 2018Marañon et al, 2014Marañon et al, , 2018.…”
Section: Total Chl-a Anomalies During the 2014-2015 Periodmentioning
confidence: 89%
See 1 more Smart Citation
“…Many of these investigations [14,25,26,28] reported the effect of these warm anomalies on sea surface temperature and phytoplankton biomass from the SCC southern region using information obtained from remote sensors. However, off the Baja California Peninsula, only the work of Linacre et al [30] and Jiménez-Quiróz et al [31] reported results regarding phytoplankton biomass and its taxonomic composition in consideration of field data from the entire water column; however, their work was based on a reduced number of cruises and a short period of time.…”
Section: Introductionmentioning
confidence: 99%
“…Anthropocene marine heatwaves are becoming increasingly intense, more frequent and longer lasting due to climate change (Oliver et al 2018;Holbrook et al 2019). These anomalous heat stress events can have severe implications for a range of marine biota, e.g., influencing shifts in zooplankton communities, declines in key groups such as krill (Jiménez-Quiroz et al 2019;Evans et al 2020;Işkın et al 2020), die-offs and reproductive failures of sea-birds (Cavole et al 2016;Jones et al 2018;Piatt et al 2020), marine mammal strandings (Cavole et al 2016), and mass coral bleaching and mortality events (Hughes et al 2018). While surveying in situ ecosystem responses to climate change disturbances are essential to assess impact, it is also very costly.…”
Section: Introductionmentioning
confidence: 99%